Tetraethylammonium L-malate 1.36-hydrate - Abdul Rahman, Mohd Basyaruddin; Jumbri, Khairulazhar; Sirat, Kamaliah; Kiab, Reza; Hoong, Kun Fun (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C8H20N+.-C4H5O5 1.36H2O, contains two independent ion pairs, with similar conformations, and three water molecules of crystallization,one water molecule haing a site-occupancy factor of 0.721 (5). Intramolecular O—H O hydrogen bonds, involving the hydroxy groups and an O atom of each carboxylate anion, generate five-membered rings involving S(5) ring motifs. In the crystal structure, molecules are linked together by water molecules through four-membered O—H O—H O—H interactions to form one-dimensional infinite chains along the a axis. Since the molecules are also linked into one-dimensional infinite chains along the b axis, molecular sheets parallel to the (001) plane are created. Overall,the crystal structure is stabilized by two intramolecular O—H O hydrogen bonds, nine intermolecular O—H O and ten C—H O hydrogen bonds.